Resilience through the COVID Pandemic: Welsh Academia-Industry Collaboration for Life Science Small-to-Medium Enterprises (SMEs) - MICHAEL WINN (Postgraduate Research Conference, 2021)
The aim of this literature review is to establish the role of academic-industry collaboration, particularly in relation to SME resilience in the Life Science sector, against the economic threat of the COVID pandemic. The significance of this paper is to introduce relevant themes by synthesising the current literature to influence future research and policy-development, under the domain of business management. The paper will first introduce the modern problem of fragmentation of the sector, and then move onto the three key themes established within the current literature that are integral to academia-industry collaboration and SME resilience to help bond the Life Sciences through (a) government support, (b) knowledge transfer, and (c) network facilitation. The results were mainly positive, with many of the social actors encouraging collaboration in Wales; however, not all enterprises in the university-led networks were satisfied with the effectiveness of supported communication or collaboration, which provides an ongoing and unanswered question about how universities can best facilitate such openly innovative activities.